Digoxin and clinical outcomes in the Global Rheumatic Heart Disease Registry. Issue 5 (12th September 2018) - Karthikeyan, Ganesan; Devasenapathy, Niveditha; Zühlke, Liesl; Engel, Mark Emmanuel; Rangarajan, Sumathy; Teo, Koon K; Mayosi, Bongani M; Yusuf, Salim
Abstract : Objective: Digoxin is widely used in patients with rheumatic heart disease (RHD) despite a lack of data on its impact on clinical outcomes. We aimed to determine the association of digoxin use on clinical outcomes in patients with RHD. Methods: We performed a retrospective analysis of the association of digoxin use with mortality at 2 years in a large RHD registry. Secondary outcomes were recurrent heart failure (HF) and hospitalisation for any cause. We assessed associations using multivariable logistic regression in the entire cohort and in subgroups of patients with atrial fibrillation (AF) and HF. We also estimated average treatment effects from propensity-adjusted analyses using inverse probability treatment weighting. Results: Information on digoxin use at baseline was available for 98.7% (3298/3343) of patients. In the overall population, digoxin was significantly associated with mortality (OR 1.63, 95% CI 1.30 to 2.04, p<0.0001) and recurrent HF (OR 1.48, 95% CI 1.07 to 2.04, p=0.019). On propensity-weighted analyses, this effect was markedly attenuated (OR 1.05, 95% CI 1.01 to 1.09, p=0.005). Patients in sinus rhythm without HF had a higher propensity-adjusted odds of death with digoxin use (OR 1.06, 95% CI 1.01 to 1.12, p=0.015), but those with both AF and HF had lower mortality (OR 0.88, 95% CI 0.80 to 0.98, p=0.019). Conclusion: Digoxin use is associated with higher mortality in patients with RHD, but this is greatly attenuated on propensity adjustment, indicating the presence of substantial treatment bias. The adjusted estimates may therefore not be reliable, and large randomised trials are needed to determine the true effect of digoxin in patients with RHD.